Current and emerging techniques for oral cancer screening and diagnosis: a review. (6th September 2021) - Bisht, Sapna R; Mishra, Pratibha; Yadav, Deep; Rawal, Rakesh; Mercado-Shekhar, Karla P
Abstract: Oral cancer causes over 350 000 deaths annually worldwide. Although most cases are in Asia, the incidence of oral cancer is rising across the world. Despite recent advances in screening methods, oral cancer remains a significant cause of mortality and morbidity. The 5-year survival rate (50%–60%) has not improved over the past several decades. Early detection and accurate diagnosis of the disease can improve the survival rate and patients' quality of life. This article provides a topical review of current and emerging techniques for screening and diagnosing oral cancer. Currently available technologies have only been moderately useful towards identifying oral cancer early, motivating the development of novel approaches to address this goal. In this article, we provide an overview of adjunctive screening aids, including biofluid (saliva and serum) diagnostics, vital staining, brush biopsy, chemiluminescence, and tissue autofluorescence. Furthermore, we discuss diagnostic imaging modalities, such as computed tomography, magnetic resonance imaging, positron emission tomography, ultrasound (including traditional B-mode imaging, color Doppler, and elastography), photoacoustics imaging, and optical coherence tomography, and artificial intelligence-based methods, which are either being used clinically or are under development for oral cancer staging. The physical and biological basis underpinning each technique are discussed, along with their advantages and limitations in the technological and clinical context. The review concludes with a discussion of the future perspectives in this rapidly evolving field.